The Cardiovascular Risks of Fostamatinib in Patients with Rheumatoid Arthritis: A Systematic Review and Meta-Analysis - Chen, Yuehong; Liu, Huan; Huang, Yupeng; Lin, Sang; Yin, Geng; Xie, Qibing (Frontiers in Pharmacology, 2021)
Objective: This systematic review and meta-analysis is aimed at assessing the risks of cardiovascular adverse events in patients with rheumatoid arthritis (RA) who have been treated with fostamatinib. Methods: The electronic databases of OVID Medline, OVID EMBASE, Cochrane Central Register of Controlled Trials, and Web of Science were searched to identify studies that reported cardiovascular events or hypertension in RA patients treated with fostamatinib. Two reviewers separately and simultaneously screened the retrieved studies based on study selection criteria, collected data and performed methodological quality assessments. The effect size of meta-analysis was estimated by the Peto odds ratio (OR) or relative risk (RR) with 95% confidence intervals (95%CI). Funnel plot was used to estimate publication bias and sensitivity analysis was performed to test the robustness of the results. Results: A total of 12 trials composed of 5618 participants with low to moderate risk of bias were included. In comparison to the placebo, the use of fostamatinib was found to elevate the risk of hypertension (RR=3.82, 95%CI 2.88–5.05) but was not associated with the risks of all-cause death (Peto OR=0.16, 95%CI 0.02–1.24), major adverse cardiovascular events (Peto OR=1.24, 95%CI 0.26–5.97), pulmonary heart disease and disease of pulmonary circulation (Peto OR=1.23, 95%CI 0.13–11.87), in addition to other forms of heart disease (Peto OR=1.96, 95%CI 0.72–5.38). Furthermore, sensitivity analysis showed no significant change in effective trends and no publication bias was found. Conclusion: Fostamatinib is associated with increased risk of hypertension; however, no increased risks of cardiovascular events were observed. Further well-planned cohort studies with large study populations and longer follow-up times are needed to elucidate the outcomes.